2019
DOI: 10.1111/ppa.13077
|View full text |Cite
|
Sign up to set email alerts
|

A review of the known unknowns in the early stages of septoria tritici blotch disease of wheat

Abstract: Septoria tritici blotch (STB) disease of wheat is caused by the fungal pathogen Zymoseptoria tritici. It is the most important foliar disease of wheat in western Europe and affects wheat cultivation worldwide. The combination of intensive fungicide usage, a polycyclic asexual life cycle and an active sexual cycle has led to the emergence of fungal strains resistant/tolerant to all the major classes of fungicides used in its control. The hallmark of this disease is a long, symptomless latent phase that precedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 94 publications
(182 reference statements)
0
17
1
Order By: Relevance
“…During plant infection, Z. tritici goes through a series of developmental stages ( Rudd et al, 2015 ). These steps are generally thought to be sequential, with germination of the spores on the leaf surface (0 -1 days post infection, =dpi), subsequent hyphal penetration of stomata (1-3 dpi), followed by mesophyll colonization (3-11 dpi) and pycnidia development in neighboring stomatal cavities (11 dpi +; Brennan et al, 2019 ). In particular, later during the infection, developmental stages, such as fruiting body formation and spore maturation) appear to follow each other in time, yet vary between different isolates of Z. tritici ( Haueisen et al, 2019 ; see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…During plant infection, Z. tritici goes through a series of developmental stages ( Rudd et al, 2015 ). These steps are generally thought to be sequential, with germination of the spores on the leaf surface (0 -1 days post infection, =dpi), subsequent hyphal penetration of stomata (1-3 dpi), followed by mesophyll colonization (3-11 dpi) and pycnidia development in neighboring stomatal cavities (11 dpi +; Brennan et al, 2019 ). In particular, later during the infection, developmental stages, such as fruiting body formation and spore maturation) appear to follow each other in time, yet vary between different isolates of Z. tritici ( Haueisen et al, 2019 ; see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Paramount to identifying novel sources of genetic resistance is the need to fully understand the life cycle of the pathogen and its interaction with the host. Approximately 3 h after contact with the leaf surface, Z. tritici spores germinate and the fungus penetrates the leaf through the stomata anywhere between 12 h and 10 days post infection (DPI) [ 14 , 15 ]. The fungus grows in the sub-stomatal cavity and spreads through the apoplast to neighbouring substomatal spaces [ 16 ], before host cells begin to die and the fungus starts to feed necrotrophically [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been suggested that the latent phase may be an artefact of evolution, as Z. tritici appears to have more genetic similarity with endophytes than other pathogens [ 18 ]. There is little evidence of nutrient acquisition from the host during the latent phase [ 14 , 19 ], confuting suggestions that the fungus is feeding biotrophically. However, the latent phase does appear to impact the asexual fecundity of the pathogen; shortening the latent phase by silencing the plant homeodomain protein TaR1 allows the disease to progress to necrotrophy earlier, but reduces asexual sporulation of the fungus [ 20 ], whereas absence of some of the Z. tritici accessory chromosomes also brings forward the switch to necrotrophy but leads to an increase in numbers of pycnidia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zymoseptoria tritici spreads to susceptible host plants by asexual pycnidiospores and sexual ascospores which, following germination, infect the wheat leaf via the stomata (reviewed in Brennan et al, 2019). The lifestyle of the fungus is characterised by a symptomless latent period which typically lasts 10–14 days post-infection (dpi) (Eyal et al, 1987).…”
Section: Introductionmentioning
confidence: 99%